Enhancing Energy Access: Mapping Biomass Resources for Sustainable Development in Nigeria - Adejumo, Ayoade (Journal of King Abdulaziz University: Engineering Sciences, 2024)
Nigeria, a major producer of petroleum in the world is currently grappling with a serious energy insufficiency as result of inactivity of her four petroleum refineries often repeated disruptions of the national electricity grid. Importation of refined petroleum products to address the energy shortage has not brought the desired relief as the subsidy regime keeps making the intervention more difficult to interpret for active participation of key players. The natural gas pipeline failure has not been of help because consumers daily seek for alternatives to natural gas utilization due to regular insufficient pressure to meet demand requirements. These, coupled with several challenges associated with fossil fuels utilization including climate change, require that Nigeria embraces biomass as an additional key driver to increase her energy mix. An extensive literature review has been carried out in this paper to identify the major biomass available in the country while their characteristics and spatial distribution are also reported. The technology required for harness to achieve significant intervention so that the present hardship facing Nigerians in accessing energy carriers that will meet up with their demand can be mitigated is identified and reported. The paper concludes that huge benefits await Nigeria if her abundant biomass resources can be trapped into the energy basket of the country